(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Export-Import (EXIM) Policy alternatively known asTrade Policy, refers to Policies adopted by a country with reference to exportsand imports. Trade; Policy can be free trade policy or protective trade policy.